2007
DOI: 10.1255/jnirs.739
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric Otoscope: A New Tool in the Diagnosis of Otitis Media

Abstract: Otitis media is one of the most common childhood ailments and, therefore, has a significant impact on public healthcare expenditure. The initial diagnosis is usually performed by a primary-care physician and is based upon otoscopy and symptomatology; the certainty of diagnosis of acute otitis media is only 58-73%. This study aimed to assess the efficacy of a spectrophotometer-based system in identifying otitis media by comparing the output from the system with the clinical diagnosis of an experienced otologist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The TM works optically like a translucent diffuser but reflects a small amount of light [8]. Reflection characteristics were earlier investigated by different authors [4,23]. For human TM, reflection characteristics were investigated for wavelengths from 400 nm to 900 nm in cadavers with and without contributions of middle ear structures behind the TM [24].…”
Section: Discussionmentioning
confidence: 99%
“…The TM works optically like a translucent diffuser but reflects a small amount of light [8]. Reflection characteristics were earlier investigated by different authors [4,23]. For human TM, reflection characteristics were investigated for wavelengths from 400 nm to 900 nm in cadavers with and without contributions of middle ear structures behind the TM [24].…”
Section: Discussionmentioning
confidence: 99%
“…Similar behavior is observed in the green plot that corresponds to the healthy tympanic membrane. As reported by Schmilovitch et al, reflectance from an eardrum with OME was lower than from a normal eardrum, therefore lower intensities were measured for the former than for the latter . In addition, the same work described a low reflectance at ~550 nm with an ascendant slope for higher wavelengths.…”
Section: Methods and Resultsmentioning
confidence: 53%
“…Optically, the TM is a translucent diffuser but reflects a small amount of light. There have been reports on the diffuse optical reflectance properties of the TM which concluded that indeed the reflectance is higher in the 400-600 nm wavelength range of the visible spectrum (17,18). Therefore, if we project white light pattern on the TM, diffuse reflections can be captured by a camera.…”
Section: Methodsmentioning
confidence: 99%